2007
DOI: 10.1016/j.bone.2006.09.030
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic consideration of epiphyseal growth: Survival responses in a taxing environment

Abstract: The goal of this review is to examine some of the metabolic features of the maturing chondrocyte within the epiphyseal growth plate. The energy status of the tissue is examined in light of the energy needs of the tissue and the availability of oxygen. The role of HIF, PHD's and other proteins concerned with transduction of the oxemic response is considered and related to chondrocyte survival in a complex extracellular matrix.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 29 publications
1
12
0
Order By: Relevance
“…Autophagy was also detected in growth plate, epiphyseal fusion, and osteoarthritis (Shapiro et al, 2008;van den Berg, 2011). Chondrocytes in these areas were under hypoxia, which mediated the evaluation of HIF1a expression, reduced mTOR activities, and then initiated autophagy (Bohensky et al, 2007;Shapiro and Srinivas, 2007). Under these circumstances, autophagy degraded harmful cytosol and organelles to promote the cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…Autophagy was also detected in growth plate, epiphyseal fusion, and osteoarthritis (Shapiro et al, 2008;van den Berg, 2011). Chondrocytes in these areas were under hypoxia, which mediated the evaluation of HIF1a expression, reduced mTOR activities, and then initiated autophagy (Bohensky et al, 2007;Shapiro and Srinivas, 2007). Under these circumstances, autophagy degraded harmful cytosol and organelles to promote the cell survival.…”
Section: Discussionmentioning
confidence: 99%
“…To test whether HIF-1␣ stabilization is essential in mediating the metabolic effects of BGP, we silenced HIF-1␣ using siRNA. Because HIF-1 is recognized as a chondrogenesis survival factor, 21,24 we refrained from blocking its activity during the long-term differentiation schedule and used the short-term model. Although treatment with purified BGP resulted in elevation of HIF-1␣ protein and mRNA within 5 to 10 minutes, silencing of HIF-1␣ counteracted this effect in both ATDC5 and MOVAS cells ( Figure 6A, B, C).…”
Section: Bgp Upregulates Genes Of Glucose Transport and Utilization Vmentioning
confidence: 99%
“…21 Therefore, BGP-induced elevation of PFK and PDK1 enzyme levels indicates metabolic conversion to the glycolytic breakdown of glucose. Concomitant with increased glycolysis, we also demonstrated that BGP inhibits the opposite process of gluconeogenesis, by decreasing the expression of glucose-6-phosphatase and phosphoenolpyruvate carboxykinase enzymes.…”
Section: Idelevich Et Al Bgp Increases Hif-1␣-dependent Metabolism E67mentioning
confidence: 99%
See 1 more Smart Citation
“…A number of workers have shown that the oxygen tension in the cartilage is low, and hence chondrocytes generate much of their metabolic energy through anaerobic glycolysis (Shapiro et al, 2005). We have argued that the environment may also activate an autophagic response in the maturing cells, which serves to maintain chondrocyte viability until the induction of the apoptosis (Shapiro and Srinivas, 2007). It is now evident that the autophagic response is seen in many cell types and serves a physiologic role in generating energy utilizing the cells’ own protein and lipid stores (Klionsky, 2005).…”
Section: Introductionmentioning
confidence: 99%